Analysis of Marketing Mix Implementation on Hajj Savings Products in Increasing Hajj Customers at Mega Syariah Bank (Case Study of Mega Syariah Bank KCP Medan Katamso) - Rizky Nabila Tanjung; Mustafa Khamal Rokan (Penerbit Jurnal Indonesia, 2022)
Basically, Marketing Mix is a marketing mix concept that puts forward elements such as promotion, price, place and product by considering the company's intended purpose, in which the implementation of a good and appropriate marketing mix will increase sales of both goods and services offered. qualitative research with case studies through a descriptive approach. The results of the study explain that the marketing mix for the Main Savings Products at Bank Mega Syariah Kcp Katamso can be categorized as successful this implementation is evidenced by the various successes of Bank Mega Syariah in getting customers both collectively and individually and this is inseparable on the performance of the operational and marketing teams who have implemented the marketing mix concept well, from the various efforts made by researchers, many have learned that something that is managed well, the results will also be good.